Estimating Inter-Generational Returns to Medical Care: New Evidence from At-Risk Newborns - Damian Clarke; Nicolás Lillo Bustos; Kathya Tapia Schythe (Institute of Labor Economics (IZA), 2022)
Targeted treatments of newborns with delicate health stocks have been shown to have considÂerable returns in terms of survival and later life outcomes. We seek to determine to what degree such treatments are transmitted across generations. We follow three generations of linked microÂ-data from Chile, and use a regression discontinuity design to study the impacts of targeted neonatal health policies based on birth weight assignment rules. While we observe wellÂ-known first genÂeration impacts of intensive treatment targeted to very low birth weight newborns, we document the surprising fact that these policies have negative impacts on measures of wellÂ-being at birth for second-Âgeneration individuals born to mothers who were treated at birth. We show that the mechÂanism which explains this is a strong impact of early life medical treatment on the likelihood that marginal treated individuals go on to give birth later in life, with receipt in the first generation conÂsiderably reverting negative gradients in early life health and eventual fertility. These new stylised facts and results suggest the longÂterm implications of health policies within family lineages may be quite different to their short term implications, placing more weight on necessary reinforcing interventions.
Keywords: I11; I18; J13; H51; O15; 330; fertility; parental investments; interÂgenerational mobility; early life interventions; health care proÂvision